2019
DOI: 10.1093/llc/fqz083
|View full text |Cite
|
Sign up to set email alerts
|

CBDR: An efficient storage repository for cultural big data

Abstract: Cultural data and information on the web are continuously increasing, evolving, and reshaping in the form of big data due to globalization, digitization, and its vast exploration, with common people realizing the importance of ancient values. Therefore, before it becomes unwieldy and too complex to manage, its integration in the form of big data repositories is essential. This article analyzes the complexity of the growing cultural data and presents a Cultural Big Data Repository as an efficient way to store a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It is observed that in 2019 the largest number of articles is concentrated. Of the 9 articles, 3 are from Springer ([ 33 , 34 , 66 ]), the publisher with the highest number of articles, as it can be observed in Figure 3 and Figure 4 ; 2 belong to ACM ([ 76 , 78 ]); 2 to IEEE ([ 35 , 96 ]), and 2 pertain to the category “Others” ([ 95 , 97 ]).…”
Section: Classification Of Research Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that in 2019 the largest number of articles is concentrated. Of the 9 articles, 3 are from Springer ([ 33 , 34 , 66 ]), the publisher with the highest number of articles, as it can be observed in Figure 3 and Figure 4 ; 2 belong to ACM ([ 76 , 78 ]); 2 to IEEE ([ 35 , 96 ]), and 2 pertain to the category “Others” ([ 95 , 97 ]).…”
Section: Classification Of Research Papersmentioning
confidence: 99%
“…The authors in [ 97 ] presented a cultural Big Data repository as an efficient way to store and retrieve cultural Big Data. The proposed repository is highly scalable and provides high performance integrated methods for Big Data analysis of cultural heritage.…”
Section: Description Of the Set Of Work By Categorymentioning
confidence: 99%